Associations between television viewing time and overall sitting time with the metabolic syndrome in older men and women: The Australian diabetes obesity and lifestyle study - Gardiner, P.; Healy, Genevieve; Eakin, E.; Clark, B.; Dunstan, D.; Shaw, J.; Zimmet, P.; Owen, N. (2011)
Objectives: To examine associations between self-reported television (TV) viewing time and overall sitting time with the metabolic syndrome and its components. Design: Cross-sectional. Setting: Population-based sample of older men and women living in Australia. Participants: One thousand nine hundred fifty-eight participants from the Australian Diabetes, Obesity and Lifestyle (AusDiab) study (aged=60, mean age 69, 54% women). Measurements: Self-reported television viewing time and overall sitting time were collected using an interviewer-administered questionnaire. The metabolic syndrome was defined according to the revised International Diabetes Federation criteria. Results: Compared with those in the lowest quartile, the odds ratios (ORs) of the metabolic syndrome in the highest quartile of television viewing time were 1.42 (95% confidence interval (CI)=0.93-2.15) for men and 1.42 (95% CI=1.01-2.01) for women and in the highest quartile of overall sitting time were 1.57 (95% CI=1.02-2.41) for men and 1.56 (95% CI=1.09-2.24) for women. Television viewing time was associated with lower high-density lipoprotein cholesterol (HDL-C) levels and glucose intolerance in women. Overall sitting time was detrimentally associated with greater risk of high triglyceride levels in men and women, abdominal obesity in women, and low HDL-C levels in men. All models were adjusted for age, education, physical activity, self-rated health, employment, diet, smoking, and alcohol intake and for hormone replacement therapy and estrogen use in women. Conclusion: For older adults, high levels of sedentary behavior were associated with greater prevalence of the metabolic syndrome; reducing prolonged overall sitting time may be a feasible way to improve metabolic health.